Subacute invasive pulmonary aspergillosis misdiagnosed as tuberculosis in a Nigerian man: A case report (Indian Journal of Case Reports, 2024)
Subacute invasive pulmonary aspergillosis is a form of chronic pulmonary aspergillosis (CPA) with rapid progression. The clinical features of CPA mimic tuberculosis (TB) and may lead to delayed and/or misdiagnosis. We report a 39-year-old Nigerian previously managed in a peripheral hospital as a case of TB despite negative Gene-X pert results with no resolution of symptoms. Chest X-ray and computer tomography findings were suggestive of CPA and galactomannan assay positive. Symptoms resolved 2 months into itraconazole treatment. There is a dire need to drive awareness of CPA among clinicians, especially in our primary and secondary healthcare facilities where the knowledge base and expertise in the management of fungal infections is still at a rudimentary level or perhaps not available at all.